Perjanjian Build Operate and Transfer (BOT) dalam Perspektif Hukum Bisnis - Israni Cahyanti; Abel Putra Beyu; Alya Amelisa; Dhio Endika Putra; Nailul Faizah Putri; Helfira Citra (Jurnal Kajian Hukum dan Pendidikan Kewarganegaraan, 2025)
Build Operate and Transfer (BOT) agreements constitute a form of cooperation between the government and private entities that is widely applied in the utilization of state or regional assets and infrastructure development. This type of agreement has emerged as an alternative financing mechanism in response to limited public funding, while also encouraging private sector participation in business activities involving public interests. However, in practice, BOT agreements often raise legal issues related to legal certainty, legal protection for the parties, and the legal consequences arising from the failure to fulfill the legal requirements of a valid contract. This study aims to analyze the role of BOT agreements in creating legal certainty and legal protection, to examine efforts to minimize legal violations in the implementation of BOT agreements, and to assess the legal consequences arising when the legal requirements of a valid contract are not fulfilled. The research employs a normative juridical method using statutory and conceptual approaches. The data were obtained through a literature study of relevant laws and regulations, particularly the Indonesian Civil Code, as well as legal doctrines and scholarly articles related to contract law and BOT agreements. The findings indicate that BOT agreements play a crucial role in ensuring legal certainty by clearly regulating the rights, obligations, and responsibilities of the parties from the construction phase to the operation and eventual transfer of assets. Furthermore, BOT agreements serve as a means of legal protection for both the government and private investors through the application of contract law principles, sanctions for breach of contract, and dispute resolution mechanisms. Nevertheless, the effectiveness of BOT agreements is highly dependent on the fulfillment of the legal requirements of a valid contract as stipulated in Article 1320 of the Indonesian Civil Code. Failure to meet these requirements may result in contracts being voidable or null and void, potentially causing significant legal and economic losses. Therefore, careful drafting and implementation of BOT agreements based on good faith principles are essential to ensure legal certainty and protection for all parties involved.